Foley catheter vs. oral misoprostol to induce labour among hypertensive women in India: a cost‐consequence analysis alongside a clinical trial. (22nd June 2018) - Leigh, S; Granby, P; Haycox, A; Mundle, S; Bracken, H; Khedikar, V; Mulik, J; Faragher, B; Easterling, T; Turner, MA; Alfirevic, Z; Winikoff, B; et al.
Abstract : Objective: To determine the effectiveness and economic impact of two methods for induction of labour in hypertensive women, in low‐resource settings. Design: Cost‐consequence analysis of a previously reported multicentre, parallel, open‐label randomised trial. Setting & population: A total of 602 women with a live fetus, aged ≥18 years requiring delivery for pre‐eclampsia or hypertension, in two public hospitals in Nagpur, India. Methods: We performed a formal economic evaluation alongside the INFORM clinical trial. Women were randomised to receive transcervical Foley catheterisation or oral misoprostol 25 mcg. Healthcare expenditure was calculated using a provider‐side microcosting approach. Main outcome measures: Rates of vaginal this delivery within 24 hours of induction, healthcare expenditure per completed treatment episode. Results: Induction with oral misoprostol resulted in a (mean difference) $20.6USD reduction in healthcare expenditure [95% CI (−) $123.59 (−) $72.49], and improved achievement of vaginal delivery within 24 hours of induction, mean difference 10% [95% CI (−2 to 17.9%), P = 0.016]. Oxytocin administration time was reduced by 135.3 minutes [95% CI (84.4–186.2 minutes), P < 0.01] and caesarean sections by 9.1% [95% CI (1.1–17%), P = 0.025] for those receiving oral misoprostol. Following probabilistic sensitivity analysis, oral misoprostol was cost‐saving in 63% of 5, 000 bootstrap replications and achieved superior rates of vaginal delivery, delivery within 24 hours of induction and vaginal delivery within 24 hours of induction in 98.7%, 90.7%, and 99.4% of bootstrap simulations. Based on univariate threshold analysis, the unit price of oral misoprostol 25 mcg could feasibly increase 31‐fold from $0.24 to $7.50 per 25 mcg tablet and remain cost‐saving. Conclusion: Compared to Foley catheterisation for the induction of high‐risk hypertensive women, oral misoprostol improves rates of vaginal delivery within 24 hours of induction and may also reduce costs. Additional research performed in other low‐resource settings is required to determine their relative cost‐effectiveness. Tweetable abstract: Oral misoprostol less costly and more effective than Foley catheter for labour induction in hypertension. Tweetable abstract: Oral misoprostol less costly and more effective than Foley catheter for labour induction in hypertension.